Isolation, molecular identification and antibiogram profiles of Escherichia coli and Salmonella spp. from diarrhoeic cattle reared in selected areas of Bangladesh - Sohidullah, M; Khan, Md Shahidur Rahman; Islam, Md Shafiqul; Islam, Md Mehedul; Rahman, Saifur; Begum, Ferdousi (Asian Journal of Medical and Biological Research, 2017)
The present research work was undertaken to find out the passive causes of occurrences of diarrhoea in terms of age, sex, season and location differences through isolation and identification of the E. coli and Salmonella spp. using cultural, biochemical and molecular from the field samples of the diarrhoeic cattle and to study the antibiogram profiles of the isolated bacterial species. Considering above purposes, a total of 57 rectal swab samples were collected from the diarrhoeic cattle of Mymensingh sadar, Trishal, Valuka, Natore sadar and Gomostapur, Chapai Nawabganj. Different types of cultural media like Nutrient agar, MacConkey`s (MC) agar, Eosin Methylene Blue (EMB) agar, Salmonella-Shigella (SS) agar, Xylose-Lysine-Deoxycholate (XLD) agar and Blood agar were used to isolate and to study the cultural properties of the E. coli and Salmonella spp. Finally Grams staining and different biochemical tests were performed to identify those two bacterial species. Out of 57 samples, 27 were positive for E. coli and 8 were positive for Salmonella spp. On the basis of information from cattle owners and clinical signs the prevalence of diarrhoea was recorded as 30.99% and the pvalue was calculated as 0.001 (p<0.01) which was noted as highly significant. The prevalence percentages of the E. coli and Salmonella spp. were differed depending on different epidemiological parameters like age, sex, season and location. Moreover, the molecular identifications were further confirmed by means of PCR assay using specific primers for E. coli and Salmonella spp. This was done targeting 16S rRNA gene where they were found to be positive showing amplification of 585 bp for E. coli and 574 bp for Salmonella spp. From the study of the antibiogram profiles, it was revealed that E. coli were susceptible to ciprofloxacin, gentamicin and norfloxacin but resistant to tetracycline, erythromycin, amoxicillin and streptomycin whereas Salmonella spp. were susceptible to ciprofloxacin, gentamicin, amoxicillin and streptomycin but resistant to azithromycin, tetracycline and erythromycin. The findings of this research work would certainly help to select the proper antibiotics against diarrhoea in cattle of Bangladesh and to overcome the multi-drug resistant problem of the bacteria. Asian J. Med. Biol. Res. December 2016, 2(4): 587-595